2020
DOI: 10.3389/fonc.2020.578921
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Dosimetric Analysis of the New ESTRO-ACROP Target Volume Delineation Guidelines for Postmastectomy Volumetric Modulated Arc Therapy After Implant-Based Immediate Breast Reconstruction

Abstract: ESTRO-ACROP) presented new guidelines for clinical target volume (CTV) delineation in post-mastectomy radiation therapy (PMRT) after implant-based immediate breast reconstruction (IBR-i). This study evaluated the dosimetric characteristics, dosimetric accuracy, and delivery accuracy of these guidelines in volumetric modulated arc therapy (VMAT).Methods and Materials: This retrospective study included 15 patients with left breast cancer who underwent mastectomy with tissue expander placement followed by PMRT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Chang et al compared the dosimetric characteristics of VMAT plans generated based on conventionally delineated clinical target volumes and volumes contoured according to ESTRO ACROP guidelines. Fifteen left-sided PMRT with IBR patients were included in this study and mammaria interna lymph nodes were covered within the target volume [ 22 ]. Hypofractionated regimen was used to a total dose of 40.05 Gy in 15 fractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al compared the dosimetric characteristics of VMAT plans generated based on conventionally delineated clinical target volumes and volumes contoured according to ESTRO ACROP guidelines. Fifteen left-sided PMRT with IBR patients were included in this study and mammaria interna lymph nodes were covered within the target volume [ 22 ]. Hypofractionated regimen was used to a total dose of 40.05 Gy in 15 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, they also reported lower mean heart doses (3.99 ± 1.02 vs. 5.84 ± 1.78 Gy, p = 0.000), however, these doses were obtained at the cost of higher CB doses. [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the 2019 ESTRO-ACROP consensus guidelines for volume delineation when treating PMRT after implantbased immediate reconstruction, 1 we envisage there may be clinicians who are keen to implement this when presented with a patient who has this ATED in-situ, given the potential to significantly reduce dose to cardiac structures when compared to conventional target volumes. 13 Minimising RT dose to the heart is well known to be beneficial when it comes to reducing the risk of major coronary or other cardiac events. 19,20 This study shows that acceptable RT plans can be generated if needing to treat left sided PMRT, targeting the chest wall and regional nodes, using DIBH and VMAT or t-IMRT technique.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The European Society of Radiation & Oncology and Advisory Committee on Radiation Oncology Practice (ESTRO-ACROP) in 2019 published a consensus guideline for target volume delineation of the chest wall for PMRT in the setting of immediate breast reconstruction, tailored to the location of the implant, 1 which will likely be increasingly utilised in the future, especially in the setting of modern RT planning techniques. It has been shown by Chang et al 13 to lead to VMAT plans with significantly lower dose to heart and left anterior descending coronary artery when compared to conventional target volume delineations which include the whole implant. The decision to include or exclude internal mammary node (IMN) in the treatment volumes continues to be a topic of clinical controversy in node positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ESTRO ACROP consensus guideline for target volume delineation for patients who received post mastectomy radiotherapy after implant-based immediate reconstruction for early stage breast cancer was published [10]. Subsequent dosimetric studies are perfomed using the new guideline, including one study which showed significant dose reduction for normal heart and left anterior descending artery with the new target volume [31]. More studies reporting the association with the new guideline and reconstruction complications are anticipated.…”
Section: Discussionmentioning
confidence: 99%